2009
DOI: 10.1007/s00464-009-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary access-related complications in laparoscopic cholecystectomy via the closed technique: experience of a single surgical team over more than 15 years

Abstract: Primary access-related complications during LC are common and can prove to be fatal if not identified early. The incidence of these injuries with closed methods is no greater than with open methods. No evidence suggests abandonment of the closed-entry method in laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…Complication reports in literature are very similar to the ones presented in our population (0.76%) [1] [4] [10]. Total incidence of vascular lesions was 0.13%, higher to the reported in general literature, but with 0% mortality.…”
Section: Discussionsupporting
confidence: 69%
“…Complication reports in literature are very similar to the ones presented in our population (0.76%) [1] [4] [10]. Total incidence of vascular lesions was 0.13%, higher to the reported in general literature, but with 0% mortality.…”
Section: Discussionsupporting
confidence: 69%
“…The bowel injuries as reported by various studies are Southern surgeons club (0.3%), Dezial et al (0.14%-0.08%), Sasmal et al (0.07%). 2,8,19 We also had a complication of duodenal injury, during the procedure which was detected at that time and was reaired at the same time with favourable outcomes. Vagenas et al reported injury to 2nd part of duodenum in one (0.08%) patient.…”
Section: Resultsmentioning
confidence: 99%
“…3 Among the different methods of primary access in laparoscopy, the popular ones being the Veress needle and Hasson's technique. 4 The Veress needle technique is still being used by many surgeons and gynecologist as an gold standard technique 5,6 while others recommend the open method of access as gold standard. Some studies have shown…”
Section: Introductionmentioning
confidence: 99%